2019
DOI: 10.1128/aac.01904-18
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, Toxicological, and Dose Range Assessment of OG716, a Novel Lantibiotic for the Treatment of Clostridium difficile -Associated Infection

Abstract: Lantibiotics present an attractive scaffold for the development of novel antibiotics. We report here a novel lantibiotic for the treatment of Clostridium difficile infection. The lead compounds were selected from a library of over 700 single-and multiple-substitution variants of the lantibiotic mutacin 1140 (MU1140). The best performers in vitro and in vivo were further used to challenge Golden Syrian hamsters orally in a Golden Syrian hamster model of Clostridium difficile-associated disease (CDAD) in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Additionally, OG716, a derivative of mutacin 1140, which is considered as a potential candidate for CDAD treatment, has shown no toxicity or side effects upon oral administration in Golden Syrian Hamster; hence, it may progress toward clinical development (Pulse et al . 2019 ).…”
Section: Evaluation Of Bacteriocin Safetymentioning
confidence: 99%
“…Additionally, OG716, a derivative of mutacin 1140, which is considered as a potential candidate for CDAD treatment, has shown no toxicity or side effects upon oral administration in Golden Syrian Hamster; hence, it may progress toward clinical development (Pulse et al . 2019 ).…”
Section: Evaluation Of Bacteriocin Safetymentioning
confidence: 99%
“…The effectiveness of OPS-2071 and other drugs was assessed in a hamster model of CDI. This model is the current gold standard used to assess potential efficacy in the treatment of CDI (26)(27)(28)(29). The survival curve for each drug tested in this study is shown in Fig.…”
Section: In Vivo Activity In the Hamstermentioning
confidence: 99%
“…With respect to the efficacy in animal models, many therapeutic agents have been tested in the hamster model of clindamycin-induced CDI (26)(27)(28)(29). Specifically, we organized our animal model with reference to an animal model in which clindamycin is administrated one day after the C. difficile infection (27), because CDI is normally induced by administration of antibiotics with on February 1, 2021 by guest http://aac.asm.org/ Downloaded from pre-existing C. difficile in the intestine. In addition, the MIC of C. difficile ATCC 43255 to clindamycin is reported as 8µg/mL (35).…”
Section: Difficile Has Been Reported As An Urgent Threat To Human Health By the Center For Diseasementioning
confidence: 99%
“…Second, the route of administration determines the onset and the duration of the pharmacological effect, the efficacy, and the adverse effects of drugs. The main routes of bacteriocin administration, such as intranasal ( McCaughey et al, 2016a , b ), intragastric ( Wongsen et al, 2019 ), intraperitoneal ( Piper et al, 2012 ; Sahoo et al, 2017 ), subcutaneous ( Kers et al, 2018a , b ; Pulse et al, 2019 ), and topical ( Van Staden et al, 2016 ; Cebrián et al, 2019 ) have demonstrated excellent efficacy in murine models. However, the efficacy of the different routes of administration has not been directly compared and likely depends on the pathogen targeted ( Lohans and Vederas, 2012 ).…”
Section: In Vivo Assessment Of Bacteriocinsmentioning
confidence: 99%